Autoimmune Diseases Acute and Complex Situations - Khamashta, Munther A.; Khamashta, Munther A.; Ramos-Casals, Manuel.; Ramos-Casals, Manuel. (Springer London : Imprint: Springer, 2011)
Autoimmune Diseases: Acute and Complex Situations provides a detailed overview of conditions associated with autoimmune diseases that are considered either life-threatening or requiring complex management. These include abdominal pain, arthritis, cutaneous ulcers, gastrointestinal hemorrhage, epilepsy, pancreatitis, stroke and white-matter CNS lesions. Autoimmune Diseases: Acute and Complex Situations addresses the latest clinical and immunological prognostic factors that may help to identify patients at higher risk of developing potentially life-threatening involvement. This book comprehensively helps the reader to diagnose these patients, in whom an early therapeutic approach is essential. Autoimmune Diseases: Acute and Complex Situations is a valuable reference tool for rheumatologists, internists, immunologists, and all the specialists involved in the multidisciplinary care of patient with rheumatic and systemic autoimmune diseases.